Discrimination and mental health of Christians in Egypt: coping trajectories and perceived posttraumatic growth - Kira, Ibrahim A. (Mental health, religion & culture, 2021)
The impact of discrimination on the Egyptian Christians minority’ mental health has never been evaluated. The current study utilised Egyptian data that included 247 Christian. The data included measures for discrimination, identity salience, interfaith spirituality, religiosity, "Will to Exist, Live and Survive" (W℡S), reappraisal, self-esteem, posttraumatic growth, collective existential annihilation anxiety (Col-EAA), psychopathology, and post traumatic stress disorder (PTSD). We conducted a T-test, stepwise regressions, and path analysis. Discrimination predicted Col-EAA and PTSD, while W℡S and spirituality were protective against Col-EAA. Discrimination had direct effects on higher Col-EAA, and indirect effects on higher PTSD, internalising and thought disorders, and negative effects on self-esteem. Col-EAA had negative effects on reappraisal, self-esteem, and positive effects on PTSD, externalising, internalising, and thought disorders. Identity salience had positive effects on reappraisal and indirect effects on self-esteem. It had indirect effects on lower externalising, internalising, and thought disorders. Discrimination negatively impacts Egyptian Christian mental health. However, their strong identity, W℡S, and interfaith spirituality are protective factors. We discussed the implications of these results from mental health and social justice perspectives.